Development of a Chinese werewolf deception database - Yang, Chaocao; You, Xuqun; Xie, Xudong; Duan, Yuanyuan; Wang, Buxue; Zhou, Yuxi; Feng, Hong; Wang, Wenjing; Fan, Ling; Huang, Genying; Shen, Xunbing (Frontiers in Psychology, 2023)
While it is important to be able to accurately detect deception, very limited research in this area has been undertaken with Asian people. We aimed to address this gap by undertaking research regarding the identification of deception in Asians in naturalistic environments. In the present work, we developed a Chinese Werewolf Deception Database (C2W2D), which consists of 168 video clips (84 deceptive ones, 84 honest ones). A total of 1,738,760 frames of facial data were recorded. Fifty-eight healthy undergraduates (24 males, 34 females) and twenty-six drug addicts (26 males) participated in a Werewolf game. The development of C2W2D was via a “Werewolf” deception game paradigm in which participants spontaneously told truths or lies. Two synced high-speed cameras were used to capture the game process. To explore the differences between lying and truth-telling in the database, descriptive statistics (e.g., duration, quantity) and hypothesis tests were conducted using action units (AUs) of facial expressions (e.g., t-test). The C2W2D contributed a relatively sizable number of deceptive and honest samples with high ecological validity. It can be used to study individual differences and the underlying mechanisms of lies and truth-telling between drug addicts and healthy people.